Investigation of Taxol biosynthetic genes for the production of novel taxanes in heterologous plant systems - Narraidoo, Nathalie (2011)
The diterpenoid paclitaxel (TaxolTM) is one of the most effective anticancer drugs, used against a wide range of cancers. It is produced as a secondary metabolite in the vascular cambial region of the bark of Taxus brevifolia from which it was first extracted in 1971. Taxol also accumulates in low concentrations in several other Taxus species. As the demands for Taxol greatly exceeded its supply, alternative routes for producing the drug and its related taxanes were developed. Taxol is presently manufactured by semisynthesis from its precursors baccatin III and 10-deacetylbaccatin III found in Taxus needles. The biosynthesis of Taxol mostly occurs via the 2-C-methyl D-erythritol 4- phosphate pathway and requires at least 19 enzymatic steps from the precursor geranylgeranyl diphosphate. This study set out to heterologously express the early genes of the Taxol biosynthetic pathway in Nicotiana tabacum for the subsequent redirection of this precursor for the synthesis of novel taxanes.